Diagnosis Pattern and Outcome of Adolescents Admitted with Recurrent Abdominal Pain in a Tertiary Care Hospital - Alam, Hossain Sahid Kamrul; Ahsan, Mohammed Rizwanul; Hoque, Md Aynal; Mamun, Abm Mahfuz Hassan Al; Ahmed, Syed Shafi (Bangladesh Journal of Child Health, 2017)
Background: Abdominal pain is very common among children and adolescents. There are many causes of recurrent abdominal pain in children, but parents may find it surprising that it is very common for there to be no clear cause identified for childhood abdominal pain even though examinations and tests have been done. Objective: This study was carried out to identify the demographic profile, causes and outcomes of adolescents admitted with recurrent abdominal pain. Methods: This Retrospective descriptive study was carried out at the Adolescent Unit of Dhaka Shishu (Children) Hospital during the period from 1st October 2015 to 31st March 2017 among 102 adolescents with history of recurrent abdominal pain after following the inclusion and exclusion criteria. Collected data were statistically analyzed with the use of the Statistical Package for Social Science (SPSS) program version 15. Results: Out of 1080 total 102 (9.44%) adolescents were admitted with recurrent abdominal pain of which majority subjects were male (57%). Urban were 61.76% and rest were rural (38.24%). The specific diagnosis pattern revealed that majority had Functional abdominal pain (44.12%) followed by Urinary tract infection (UTI) (20.59%), Peptic ulcer diseases (13.73%), Gastroesophagial reflux diseases (GERD) (11.76%), Abdominal tuberculosis (5.88%), Pelvic inflammatory diseases (4.90%), Cholecystitis (1.96%) and Abdominal migraine (0.98%). Conclusion: Recurrent abdominal pain is common among adolescents. Functional abdominal pain is the most common cause of recurrent abdominal pain. An uniform management protocol should be developed for proper investigations to minimize the cost and for judicious use of drugs in order to help these adolescents with recurrent abdominal pain. Bangladesh J Child Health 2017; VOL 41 (1) :4-8